Travelista.ph a feasibility study on offering an online booking assistant in the Philippines - Casibo, Mikhail Andre; Godoy, Keane Jorren; Gonzales, Adrielli Santino; Guevarra, Millard
The advent of tourism in the Philippines started as early as the 1970's. This period was considered to be the boom of the tourism industry and it was not until 1980 that the trend dwindled down. It was in 1990 that tourism started to pick up once again and it hasn't stopped since then. The beginning of the 21st century saw 2.2 million tourists visit the Philippines. Further reinforcements in the tourism industry were followed during the next couple of years because of the emergence of abundance in tourists. With the Philippine economy slowly beginning to stabilize, new opportunities are being realized, along with the potential of the tourism industry. It holds great promise for the Philippine economy, since the backbone of a strong national economy must come from within its own borders. Having established the position of tourism in enriching the country, Travelista-ph was spawned. Travelista.ph is an online travel booking assistant capitalizing on the present technology such as the internet and various untapped and exotic locales scattered across the Philippine islands. It will also capitalize on medical tourism. Market demand is established by identifying key indicators. The explosion of technology and the vast usage of the internet coupled with the ever-increasing demand for travel show that there is a window of opportunity for the business. Moreover, customers feel the need for a better, more flexible and more accessible portal. Travelista.ph will position itself as the primary booking website of the Philippines. The services will require essentially, a website with commercial capabilities. A specific type of software is required and is the pillar of the entire service. The software is known as GDS/CRS/IBE package. The CRS or computer registration system acts as the back-end of the system allowing Travelista.ph to interact with different retailers while the IBE or internet booking engine acts as the front-end which interacts with the customer. Financial projections for the next five years were considered and with reasonable assumptions of increasing yearly demand providing revenue of PhP800,000 at year 1 and up to PhP6,000,000 in year 5. Considering all costs. Travelista.ph still yields a positive NPV at year 5 as well as a high IRR with a payback period of 3 years. Results of the study revealed a great market opportunity for the service.